2022
DOI: 10.3390/v14061146
|View full text |Cite
|
Sign up to set email alerts
|

Secretory Profile of Adipose-Tissue-Derived Mesenchymal Stem Cells from Cats with Calicivirus-Positive Severe Chronic Gingivostomatitis

Abstract: The feline calicivirus (FCV) causes infections in cats all over the world and seems to be related to a broad variety of clinical presentations, such as feline chronic gingivostomatitis (FCGS), a severe oral pathology in cats. Although its etiopathogeny is largely unknown, FCV infection is likely to be a main predisposing factor for developing this pathology. During recent years, new strategies for treating FCGS have been proposed, based on the use of mesenchymal stem cells (MSC) and their regenerative and immu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 56 publications
0
3
0
Order By: Relevance
“…The SDAI index and COPS C/F scale are partially validated assessment tools. However, the SDAI is the clinical assessment tool mostly used in FCGS studies [2,[27][28][29][30][31], and the COPS C/F is the only pain score developed to evaluate oral pain [13]. Variability between the groups resulted from the small sample size, among other factors.…”
Section: Discussionmentioning
confidence: 99%
“…The SDAI index and COPS C/F scale are partially validated assessment tools. However, the SDAI is the clinical assessment tool mostly used in FCGS studies [2,[27][28][29][30][31], and the COPS C/F is the only pain score developed to evaluate oral pain [13]. Variability between the groups resulted from the small sample size, among other factors.…”
Section: Discussionmentioning
confidence: 99%
“…Immunophenotyping of isolated ADSCs showed that, depending on the anatomical location, differences in the expression of surface markers were disclosed ( Table 2 ). SCAT-derived cells exhibited high expression of CD90, CD44, CD29, CD105, CD73, MHC class I, and CD9, and minimal or absent CD34, CD45, MHC class II, CD14, and CD4 expression [ 74 , 76 , 77 , 78 , 80 , 81 , 82 , 83 , 107 ]. Conversely, cells from the different anatomical locations of VAT showed heightened expression of CD90, CD44, CD29 (falciform ligament), and CD105, while CD34, CD45, MHC class II, and CD14 expression was limited or absent [ 75 , 79 ].…”
Section: Harvesting Location Influence On Adscs’ Biological Profilementioning
confidence: 99%
“…The presence of other inflammatory disorders could also be important; a large FCGS case series found that cases with TR had a more favorable outcome, and that both PD and TR were associated with alveolar bone loss. From a molecular standpoint, transcriptome (e.g., gene expression of Janus kinase (JAK)-signal transducer and activator of transcription (STAT) pathway, interleukin-17, interleukin-6) and proteome (e.g., proinflammatory cytokines) biomarkers of FCGS were recently reported [9,10].…”
Section: Introductionmentioning
confidence: 99%